Effect of Spironolactone on COVID-19 in Patients With Underlying Liver Cirrhosis: A Nationwide Case-Control Study in South Korea - Jeon, Dongsub; Son, Minkook; Choi, Jonggi (Frontiers in Medicine, 2021)
Purpose: On the basis that spironolactone is involved in ACE2 expression and TMPRSS2 activity, previous studies have suggested that spironolactone may influence the infectivity of COVID-19. Research has suggested that cell entry of SARS-CoV-2, the virus that induces COVID-19, is associated with the ACE2 receptor and TMPRSS2. The purpose of this study was to investigate whether spironolactone has a protective effect against COVID-19 and the development of associated complications in patients with liver cirrhosis. Methods: We conducted a nationwide case-control study on liver cirrhosis patients with or without COVID-19 from the population-based data acquired from the National Health Insurance Systems of Republic of Korea. After 1:5 case-control matching, multivariable adjusted conditional logistic regression analysis was performed. Results: Among the patients with liver cirrhosis, the case group with COVID-19 was found to be significantly less exposed to spironolactone compared with the control group without COVID-19. The adjusted odds ratio (OR) and 95% confidence interval (CI) between the two groups was 0.20 (0.07–0.54). In addition, regardless of cumulative dose of spironolactone, exposure to spironolactone was associated with lower COVID-19 infection. In terms of the development of complications due to COVID-19, spironolactone did not show any significant association between the patients with and without complications (P = 0.43). The adjusted OR and 95% CI between the two groups was 1.714 (0.246–11.938). Conclusion: We conclude that spironolactone may reduce susceptibility to COVID-19 but does not affect the development of its associated complications; however, further studies are needed to confirm the exact association between spironolactone and COVID-19 infection.